Guanine base stacking in G-quadruplex nucleic acids - Lech, Christopher Jacques (2013)
G-quadruplexes constitute a class of nucleic acid structures defined by stacked guanine tetrads (or G-tetrads) with guanine bases from neighboring tetrads stacking with one another within the G-tetrad core. Individual G-quadruplexes can also stack with one another at their G-tetrad interface leading to higher-order structures as observed in telomeric repeat-containing DNA and RNA. In this study, we investigate how guanine base stacking influences the stability of G-quadruplexes and their stacked higher-order structures. A structural survey of the Protein Data Bank is conducted to characterize experimentally observed guanine base stacking geometries within the core of G-quadruplexes and at the interface between stacked G-quadruplex structures. We couple this survey with a systematic computational examination of stacked G-tetrad energy landscapes using quantum mechanical computations. Energy calculations of stacked G-tetrads reveal large energy differences of up to 12 kcal/mol between experimentally observed geometries at the interface of stacked G-quadruplexes. Energy landscapes are also computed using an AMBER molecular mechanics description of stacking energy and are shown to agree quite well with quantum mechanical calculated landscapes. Molecular dynamics simulations provide a structural explanation for the experimentally observed preference of parallel G-quadruplexes to stack in a 5′–5′ manner based on different accessible tetrad stacking modes at the stacking interfaces of 5′–5′ and 3′–3′ stacked G-quadruplexes.